The equation 4[x + 2(3x −7 )] = 22x − 65 was simplified to write the equivalent equation of 28x-56=22x-65.

What is the solution of the equation
4[x + 2(3x – 7)] = 22x – 65?

Respuesta :

Answer:

  x = -3/2

Step-by-step explanation:

Starting from the simplified form, we can subtract 22x to get ...

  6x -56 = -65

  6x = -9 . . . . . . . . add 56

  x = -9/6 = -3/2 . . . . divide by 6 and simplify

The solution of the equation is x = -3/2.

_____

Check

Substituting -3/2 for x in the original equation, we get ...

  4[-3/2 +2(3(-3/2) -7)] = 22(-3/2) -65

  4[-3/2 +2(-23/2)] = -33 -65

  4[-3/2 -23] = -98

  4[-49/2] = -98 . . . . . . . true